Identification of a rhodium(iii) complex as a Wee1 inhibitor against TP53-mutated triple-negative breast cancer cells. Issue 20 (25th January 2018) - Yang, Guan-Jun; Zhong, Hai-Jing; Ko, Chung-Nga; Wong, Suk-Yu; Vellaisamy, Kasipandi; Ye, Min; Ma, Dik-Lung; Leung, Chung-Hang
Abstract : The rhodium(iii ) complex1 was identified as a potent Wee1 inhibitor in vitro and in cellulo . Abstract : The rhodium(iii ) complex1 was identified as a potent Wee1 inhibitor in vitro and in cellulo . It decreased Wee1 activity and unscheduled mitotic entry, and induced cell damage and death in TP53 -mutated triple-negative breast cancer cells.1 represents a promising scaffold for further development of more potent metal-based Wee1 antagonists.